Pengembangan Media Pembelajaran Majalah Fisika sebagai Suplemen Pembelajaran Terintegrasi Nilai Keislaman - Selviani, Siska; Anggraini, Welly (Universitas Islam Negeri Raden Intan Lampung, 2018)
Abstract: This research is motivated by the provision of ability through instructional media based on the values of Islamic teachings. Not yet used learning media as an integrated learning supplement of Islamic values. This study aims to develop, know the feasibility and know the response of educators and learners to the media learning physics magazine as an integrated learning supplement Islamic values. This research method is Research and Developmen (R and D). This research product in the form of learning media of physics magazine as an integrated learning supplement of Islamic values, and feasibility result obtained by media expert 83%, material expert 85%, and religious material expert 80% highly deserved. Positive response from educators with 88.05% percentage. 91% individual test results, small group trial 89.52%, and field trials 91% of the three test results gave a positive response. The development of learning media of physics magazine as an integrated learning supplement of Islamic values is very feasible and get a positive response to be used as learning media. Abstrak : Penelitian ini dilatarbelakangi oleh pembekalan kemampuan melalui media pembelajaran dengan basis pada nilai-nilai ajaran islam. Belum digunakannya media pembelajaran sebagai suplemen pembelajaran yang terintegrasi nilai keislaman. Penelitian ini bertujuan untuk mengembangkan, mengetahui kelayakan dan mengetahui respon pendidik dan peserta didik terhadap media pembelajaran majalah fisika sebagai suplemen pembelajaran terintegrasi nilai keislaman. Metode penelitian ini yaitu Research and Developmen (R and D). Produk penelitian ini berupa media pembelajaran majalah fisika sebagai suplemen pembelajaran terintegrasi nilai keislaman, dan hasil kelayakan diperoleh ahli media 83%, ahli materi 85%, dan ahli materi agama 80% dikriteriakan sangat layak. Respon positif dari pendidik dengan persentase 88,05%. Hasil uji coba perorangan 91%, uji coba kelompok kecil 89,52%, dan uji coba lapangan 91% ketiga hasil uji coba memberikan respon positif. Pengembangan media pembelajaran majalah fisika sebagai suplemen pembelajaran terintegrasi nilai keislaman sangat layak dan mendapat respon positif untuk dijadikan media pembelajaran.